Vulnerability Of Smallholder Maize Farming Households To Climate Variability In The Eastern Region Of Ghana - Sadiq, M.A. (University of Ghana, 2016)
Climate change and variability is one of the great challenges facing farming households in Ghana. The main objective of this study is to assess the vulnerability of smallholder maize farming households to climate variability in the Eastern region. Specifically, the study investigates the vulnerability of households to climate variability, the determinants of households’ livelihood vulnerability level, the adoption level of adaptation strategies to climate variability and the determinants of the choice of those strategies and finally households’ constraints to climate variability adaptation strategies in the Yilo Krobo Municipality and Ayensuano District in the Eastern Region of Ghana. Primary data was collected using structured questionnaires and focus group discussions whereas the Secondary data for climate were collected from the Meteorological Agency, Ghana. Fifteen (15) respondents each were sampled randomly from 10 communities making 150 respondents. The Livelihood Vulnerability Index (LVI) is used to analyze households’ vulnerability to climate variability while Generalized Least Square is used to estimate the determinants of household vulnerability level. Multinomial Logistic regression model is employed for the determinants of the choice of adaptation strategies. The main software used is Stata (13). The results of the LVI score for Yilo Krobo is 0.363 and that of Ayensuano is 0.390 while the LVI-IPCC is 0.028 for Yilo Krobo and 0.031 for Ayensuano, all the two approaches indicating that households in Ayensuano are most vulnerable to the impacts of climate variability. Both Ayensuano and Yilo Krobo are most vulnerable in the natural disaster and climate variability component (0.528 for Ayensuano and 0.459 for Yilo Krobo) but least vulnerable in food component of the LVI (0.227 for Ayensuano and 0.202 for Yilo Krobo). The results of the GLS regression show gender, farm size, access to credit and temperature perception to be the factors that statistically influence household vulnerability in Yilo Krobo while farming experience, formal extension and hired labour are found to significantly influence vulnerability of households in Ayensuano district. The pooled sample show farming experience, access to credit, formal extension, temperature perception and hired labour to be the determinants of households’ vulnerability level. The most adopted climate adaptation option in the area is found to be improved varieties and breeds strategies (38%) follow by recommended agricultural practice strategies (36%) with soil related strategies been the least adopted adaptation strategies (27%). The parameter estimates of the MNL regression model show rainfall perception, access to credit and farming experience to be influencing the choice of recommended agricultural practices while that of soil related strategies are gender and rainfall perception. Farming experience and rainfall perception are the factors that influenced the choice of improved varieties and breeds strategies. The empirical results of the Kendall’s ranking show there is agreement among the ranking of constraints by the respondents. The most pressing constraints identified in the study area are inadequate and limited access to credit, inadequate drought tolerant varieties and low literacy. However, inadequate knowledge on climate related strategies and poor extension are the least ranked constraints in the study area. Water supply should be improved in Yilo Krobo municipality through the construction of potable water sources such as boreholes and wells in order to reduce the vulnerability of households to climate variability. Further, farmers in the region should be provided with improved varieties of maize that can withstand droughts. Ayensuano District Assembly should assist to establish community financial co-operative in order to promote savings and investment which can lead to a reduction in level of vulnerability financially and help to build social networks. Weather stations should be installed in the two districts to aid in the dissemination of information on any impending natural disasters to farmers.
Thesis (MPhil)
Keywords: Vulnerability; Smallholder Maize Farming; Households; Climate Variability; Eastern Region; Ghana